Information structure and language change : new approaches to word order variation in Germanic - Hinterhölzl, Roland; Petrova, Svetlana, 1969- (Trends in linguistics. Studies and monographs ;, 2009)
The volume presents new approaches to explaining word order variation and change in the Germanic languages and thus relates to one of the most prominent and widely discussed topics in the theory of language change and diachronic syntax. The novelty of our approach consists in three main points. First of all, we aim at describing functional variety in the field of word order and verb placement in the early Germanic languages not as a result of language contact, but rather as a language-internal phenomenon related to stylistic and grammatical conditions in information packaging. Second, given tha.